Lipid Polymeric Hybrid Nanoparticles: Formulation Techniques and Effects on Glioblastoma - Yudhishtir Singh Baghel; Sankha Bhattacharya (Tabriz University of Medical Sciences, 2022)
In the pharmaceutical industry, liposomes and polymeric nanoparticles are the two most commonly studied delivery vehicles. A new technique uses lipid-polymeric hybrid nanoparticles (LPHNPs) with a polymeric core, and a shell made up of lipid-lipid-PEG lipids. They have properties which complement polymer nanoparticles and liposomes, and they have the potential to improve the physical stability and biocompatibility of the active pharmaceutical ingredient encapsulated in them. Evaporating the solvent from a dual-phase solution containing lipid and polymer is one of the most effective methods for producing lipid polymeric hybrid nanoparticles. The LPHNPs applications have also been significantly expanded to include combinational and active targeted drug delivery, as well as delivery of genetic materials, vaccines, and diagnostic imaging agents, in addition to single drug delivery for anticancer therapy, like Glioblastoma. The main agenda of this compilation was to address the effects of LPHNPs on Glioblastoma treatment. This compilation also highlights some of the formulation techniques and issues that arise during the preparation of LPHNPs. This review also discusses recent developments in core-shell lipid-polymer hybrid nanoparticles, which were conferred in considerable detail later in this article. The main issue which arises while using nanoparticles with polymer is entrapment efficiency. Because of their hybrid components, LPHNPs have proven to solve this problem to a large extent. The recent research trends suggest that lipid polymeric hybrid nanoparticles will prove to be highly effective or productive in treating diseases such as Glioblastoma.